Measurement of optimal stretchability graphene conductive ink pattern by numerical analysis - Salim, Mohd Azli; Ab Wahid, Ameeruz Kamal; Masripan, Nor Azmmi; Md. Saad, Adzni; Ali, Murni; Dai, Feng (Science and Technology Research Institute for Defence, 2021)
This study determines the optimal stretchability performance of graphene conductive patterns by using maximum principal elastic strain and Von Mises stress analysis. It was performed by using experimental and finite element analysis (FEA) modelling approaches. The experimental work was initiated by obtaining the optimal formulation of the conductive ink based on the resistivity values and 20 wt.% of graphene nanoplatelets (GNP) was selected. Then, the Young’s modulus and Hardness values for this formulation were determined to become the input for the FEA modelling. Six different types ofpattern were developed for FEA analysis, which are the straight-line, sine wave, semi-circle, serpentine, zigzag and horseshoe as the straight-line pattern becomes the baseline. The sine wave pattern produced the best results as the percentage different with the baseline pattern in terms of maximum principal elastic strain and Von Mises stress were the largest with the value of 37 times lower. This is due to the fact that the sine wave has more edge and depicts the spring-like behaviour which produces better stretchability. The increased length of the pattern also contributes to stretchability performance. Furthermore, this study shows that the FEA approach can be utilised in investigating the stretchability performance of conductive ink.